Capping stability of Mg‐implanted GaN layers grown on silicon. Issue 4 (8th November 2016) - Lardeau‐Falcy, Aurélien; Coig, Marianne; Charles, Matthew; Licitra, Christophe; Baines, Yannick; Eymery, Joël; Mazen, Frédéric
Abstract : The morphological stability during activation annealing of Mg‐implanted GaN layers (2 μm thick) grown on Si (111) is studied for several protective layers and fluencies in the 10 13 –10 15 at. cm −2 range. We show that a thin capping, composed of a few nanometer thick AlN and SiN x stacks grown in situ just after GaN deposition, provides a good solution to retain flat morphology and no strain cracking up to 1 h annealing at 1100 °C in N2 . These results are compared to thicker protective stackings with AlN layers of Si3 N4 or SiO2 deposited after the implantation that withstand a thermal budget of up to 1 h at 1200 °C in N2 . The efficiency of these different cap layers to limit GaN damage during high‐temperature annealing is studied as well as the impact of Mg implantation process on the cap resilience. The quality of the GaN sublayer is studied by low‐temperature photoluminescence to analyze structural/optical defects and Mg related complexes. X‐ray diffraction is performed to evaluate residual strains at the different process stages.